Analysis of Changes in Investment Placement Strategies of Life Insurance Companies on Indonesia from January 2020 to December 2023 - Benazir, Mariam; Suardi, Lenny (Jurnal Indonesia Sosial Sains, 2026)
The life insurance sector is still striving to expand in Indonesia, while a number of macroeconomic and regulatory changes are also taking place. These developments compel the sector to adjust its strategies to remain profitable and continue expanding while complying with laws and regulations. In the midst of shifting industry conditions between early 2020 and late 2023, the author observes a notable shift in investment patterns among Indonesian life insurance companies and examines these circumstances as well as their causes. This journal employs qualitative methodologies by analyzing data consisting of investment asset portfolio information and investment returns for Indonesian life insurance companies. Observations and in-depth interviews were conducted with key investment personnel in several life insurance firms to identify the variables impacting investment strategy adjustments made by Indonesian life insurance companies during the aforementioned period. The study also evaluates the effect that these strategic shifts have on total investment income and the commensurability between the companies’ assets and liabilities. According to the analysis and observations, several factors—such as modifications to tax laws governing bond investments, adjustments to regulations applicable to life insurance companies, and a decline in unit-linked product sales—have driven these changes. In light of these conditions, there is a pressing need for more detailed regulations governing investment strategy mechanisms and pricing provisions related to investments.